Evaluation of the Antioxidant and Anticancer Effectiveness of Some New Metal Ions Complexes with Azo Dye: Synthesis and Characterization - Jirjees, Vian Yamin; Al-Hamdan, Abbas Ali (Indonesian Journal of Chemistry, 2025)
This paper presents a new azo dye 3-[2-(1H-indol-2-yl)ethyldiazenyl]quinolin-2-ol] from the reaction of the diazonium salt derived from tryptamine and 2-hydroxyquinoline. Azo dye was used to prepare a series of complexes with the chlorides of Ni(II), Pt(IV), Pd(II), Cd(II), and Zn(II). Compounds were analyzed and characterized using elemental analysis, magnetic measurement, UV-vis, IR, MS, NMR, and conductivity. The findings demonstrated that the ligand acts as ionic in complex form, O-bidentate, supporting the proposed formula. The complexes generally exhibited tetrahedral and octahedral geometries, except the palladium complex, which adopted a square planar geometry. TGA was used to investigate the thermal characteristics of compounds. The ligand dissociated in a single step, whereas the complexes dissociated through multiple steps, exhibiting greater thermal stability than the ligand. This study explored the antioxidant and anticancer activities of compounds. The results indicate that compounds are more effective in scavenging free radicals, as measured by their IC50 values, and determined the order of inhibitory effect of compounds to be gallic acid > [Ni(L)2(H2O)2] > [Pt(L)2Cl2] > [Pd(L)2] >ligand > [Cd(L)2] > [Zn(L)2]. The ligand showed significant anticancer activity, with a lower IC50 value of 49.86 μg/mL than the complexes, indicating greater efficacy against cancer cells MCF-7.